Aproximación Psicoanalítica a los Discursos Que Generan Identificación Del Pueblo Colombiano, con dos Dirigentes Políticos Victimas de La Violencia: Álvaro Uribe Vélez E Ivan Cepeda Castro (2015)
The armed conflict in Colombia is a circumstance which is repeated in the recent history of our country, giving as result that the majority of population in Colombia has been victims of violence, although they have not been attacked directly, they have lived near violence. This is the case both of Alvaro Uribe, who was president of Colombia and current senator and Ivan Cepeda Castro, who was chamber of Representatives and also senator of the republic of Colombia at the present time. The two leaders have different political views and mobilize large numbers of people in Colombia .The objective of this research is known as the Colombian population is identified in the discourse of the two political leaders For this, the theoretical approach was used is the psychoanalytic theory having as hypothesis, the transcendence of the father and the murder of both for: Alvaro Uribe and Ivan Cepeda, and how these influence the formation of their speech and the position taken against violence.